SISTEM INFORMASI PENGGAJIAN PADA J&T CARGO CABANG JATINAGOR BERBASIS VBA MICROSOFT EXCEL - Soraya, Raihan; Ginting, Gerinata (Jurnal Mahasiswa Terapan; Vol 1 No 2 (2025): Jurnal Mahasiswa Terapan, 2025)
This research aims to analyze, design, implement and test a Payroll information system that suits the needs of J&T Cargo Jatingor branch to facilitate the company's operational activities. The system development method used is the Waterfall method with research instruments including observation, interviews, documentation, and literature study. The analysis method used is PIECES analysis. The system design is made using process modeling in the form of Flowchart and Context Diagram (DK). The programming language used is Microsoft Excel VBA as a database system. The results showed that the Payroll information system on the needs of J & T Cargo Jatingor branch was not neatly recorded and there were no documents used such as Payroll. this can lead to many errors in Payroll information so that the information is not precise and accurate. Designing a Payroll information system using Microsoft Excel VBA can make it easier for owners to find out Payroll at the company. In the form of payroll report output and pay slip. This system, users only input payroll data into the system then data processing will be carried out by the system until the report is generated.